Pengaruh Penggunaan Media Flash Cards terhadap Penguasaan Kosakata Bahasa Inggris Anak Usia 4-5 Tahun di TK Percontohan Tahun Ajaran 2021-2022 - Shafira Shafira; Aminda Tri Handayani (Education & Learning, 2022)
The formulation of the problem in this study, among others, namely "Is there any effect of using flash cards media on English vocabulary mastery of children aged 4-5 years in Pilot Kindergarten?". This type of research includes True Experimental Design research, namely Posttest Only Control Group Design. The population in this study were all kindergarten children in group B in TK PILOT, totaling 50 children, consisting of 2 classes, namely B-1 totaling 25 children and B-2 totaling 25 children with a sample of class B-1 totaling 25 children. (15 women & 10 men) who were treated with tape recorder media. The instrument used in this study was a structured observation of children's English vocabulary mastery. After the data is collected, then the next step is to test the hypothesis using a one-party t test with a real level of = 0.05. Based on the data from the observation of the use of flash cards on the mastery of English vocabulary, it was found that the mastery of the children's English vocabulary was in the good category. Based on the results of observations of the use of tape recorder media on the mastery of English vocabulary, it was found that the mastery of the children's English vocabulary was quite good. This shows that the level of mastery of English vocabulary of children in the flash card media class using flash cards media is better developed than the children in the tape recorder media class using a tape recorder media. Based on the results of the t-test obtained 8.86 while 1.69, it can be concluded that there is a significant effect of the use of flash cards media on the mastery of children's English vocabulary in Santa Lusia Sei Rattan Kindergarten.